Synergistic effects of PM2.5 components and ozone exposure on lung function in young adults: A cohort study in Shandong, China - Wenfeng Kang; Jia Zhang; Xiaoyan Wang; Yun Mu; Wenxiu Zheng; Yajuan Zhang; Mingyu Feng; Zhenzhong Wang; Yi Liu; Xiaoshuai Zhang; Peng Lu (Ecotoxicology and Environmental Safety)
Exposure to fine particulate matter (PM2.5) components and ozone (O3) is associated with reduced lung function. This study aimed to examine the interaction effects of PM2.5 components and O3 on lung function in young adults. A cohort study involving 1697 participants was conducted in Shandong Province, China from September 2019 to November 2020. Pollutant data were obtained from the China High Air Pollutants (CHAP) dataset and the Tracking Air Pollution in China (TAP) dataset. Forced Vital Capacity (FVC), first-second forceful expiratory volume (FEV1.0), peak expiratory flow rate (PEF) and 50 % forceful expiratory flow rate (FEF50 %) were used as lung function indices. A linear mixed-effects model was employed to evaluate the impact of PM2.5 components and its interaction effects with O3 on lung function. Each 1 μg/m³ increase in black carbon (BC) concentration was significantly associated with 0.4027 L/s decrease in PEF (95 % confidence interval (CI): 0.2420 L/s, 0.5634 L/s). Increases in other PM2.5 components were also associated with various reduced lung function indices. Notably, the interaction term for BC and O3 was significantly associated with reduced PEF (-0.0243, 95 % CI: −0.0472, −0.0014). Synergistic effects between PM2.5 components [organic matter (OM), nitrate (NO3-)] and O3 adversely impacted lung function. A more proactive policy should be adopted to address the synergistic effects of air pollution.